Role of the sphingomyelinase Isc1p in the regulation of iron homeostasis in Saccharomyces cerevisia - Martins, Telma Filipa da Silva (2018)
Iron is an essential element for cell viability since it is a component of several metalloproteins, containing iron-sulfur clusters and heme centers. The ability to gain and lose electrons, switching between the ferrous (Fe2+) and ferric (Fe3+) states, renders the involvement of iron in many cellular processes. Iron acquisition systems have to be highly regulated to assure a continuous supply of iron but simultaneously prevent its toxicity associated with the formation of hydroxyl radicals by the Fenton reaction. Loss of iron homeostasis is behind many pathologies, highlighting the importance of understanding the mechanisms involved in iron homeostasis. The Saccharomyces cerevisiae inositolphosphosphingolipid phospholipase C (Isc1p) hydrolyses complex sphingolipids to produce ceramide, a bioactive sphingolipid. ISC1 deletion is characterized by premature aging, oxidative stress sensitivity and mitochondrial dysfunction. This mutant also exhibits an up regulation of genes involved in iron uptake leading to increased levels of iron. However the growth phase in which iron accumulation occurs, the specific site of accumulation or even the oxidation state of the accumulated iron in isc1Δ cells remains uncharacterized. Futhermore, the molecular mechanisms behind the iron overload in isc1Δ cells are not known. By monitoring iron levels and oxidation state along growth, it was possible to observe that deletion of ISC1 caused iron accumulation in all phases of growth in both the ferric and ferrous forms. Additionally to the increased iron levels, isc1Δ cells also exhibited an altered distribution of iron within the cell. Unlike wild type, isc1Δ cells did not accumulate ferric iron in the vacuole, but instead, iron seemed to be distributed throughout the cell. Furthermore, iron accumulation in isc1Δ cells was associated with the activation of Aft1p, the low iron-sensing transcriptional activator. Cells lacking Isc1p exhibed higher levels of Aft1p retained in the nucleus, and AFT1 deletion abolished iron accumulation in the isc1Δ mutant. It was also found that dephosphorylation of Aft1p in isc1Δ cells is associated with its activation. Additionally the activation of the phosphatase Sit4p in isc1Δ cells was discarded as a potential mechanism behind Aft1p dephosphorylation and activation, since isc1Δsit4Δ cells still exhibit iron overload. Overall, these results indicate that the dephosphorylation and activation of Aft1p is the factor behind the accumulation of iron in the isc1Δ mutant and reinforce the role of Isc1p in the regulation of iron homeostasis.